Long-term influence (1982–2023) of the introduced parasitoid Torymus sinensis (Hymenoptera: Torymidae) on the invasive pest, the chestnut gall wasp Dryocosmus kuriphilus (Hymenoptera: Cynipidae), at a starting point of the classical biological control in Japan - Moriya, Seiichi; Shiga, Masakazu; Adachi, Ishizue; Kishimoto, Hidenari; Mishiro, Koji; Ihara, Fumio; Yamanaka, Masahiro; Shimoda, Takeshi; Yara, Kaori (Applied entomology and zoology, 2024)
Although classical biological controls aim to permanently minimize numbers of invasive pests using exotic natural enemies, few long-term studies have been conducted on this subject. In this study, we investigated the population dynamics of the chestnut gall wasp Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae), and an introduced parasitoid, Torymus sinensis Kamijo (Hymenoptera: Torymidae), over 40 years (1982–2023) at a site at which the parasitoid was first released (Tsukuba City, Ibaraki Prefecture) in Japan. Because the gall formation rate per 100 chestnut buds, an indicator of pest density, had decreased from 42.5 to 0.7% in the first 10 years after the release, the biocontrol program was deemed successful. However, further research showed fluctuations in the pest density over the next 30 years. It usually remained at low levels but occasionally increased dramatically, with three peaks exceeding the economic injury level (30%). Simultaneously, an indicator of parasitoid density (the number of parasitoids emerging from 100 galls × the gall formation rate) also fluctuated, in synchronization with the pest density indicator. These results suggest that T. sinensis has played an important role in suppressing D. kuriphilus at the releasing site over 40 years.